Genetic diversity and population structure of Leishmania (Viannia) braziliensis in the Peruvian jungle. - Maxy B De Los Santos; Ivonne Melissa Ramírez; Jorge E Rodríguez; Peter Beerli; Hugo O Valdivia (Public Library of Science (PLoS), 2022)
Background Human cutaneous leishmaniasis caused by Leishmania (Viannia) braziliensis is highly prevalent in the Peruvian jungle, where it affects military forces deployed to fight against drug trafficking and civilian people that migrate from the highland to the lowland jungle for economic activities such as mining, agriculture, construction, and chestnut harvest. We explored the genetic diversity and population structure of 124 L. (V.) braziliensis isolates collected from the highland (Junín, Cusco, and Ayacucho) and lowland Peruvian jungle (Loreto, Ucayali, and Madre de Dios). All samples were genotyped using Multilocus Microsatellite Typing (MLMT) of ten highly polymorphic markers. Principal findings High polymorphism and genetic diversity were found in Peruvian isolates of L. (V.) braziliensis. Most markers are not in Hardy-Weinberg equilibrium; this deviation is most likely caused by local inbreeding, as shown by the positive FIS values. Linkage Disequilibrium in subpopulations was not strong, suggesting the reproduction was not strictly clonal. Likewise, for the first time, two genetic clusters of this parasite were determined, distributed in both areas of the Peruvian jungle, which suggested a possible recent colonization event of the highland jungle from the lowland jungle. Conclusions L. (V.) braziliensis exhibits considerable genetic diversity with two different clusters in the Peruvian jungle. Migration analysis suggested a colonization event between geographical areas of distribution. Although no human migration was observed at the time of sampling, earlier displacement of humans, reservoirs, or vectors could have been responsible for the parasite spread in both regions.